Efeitos da disponibilidade hídrica e de diferentes condições de irradiância sobre o crescimento, características fotossintéticas e o acúmulo de óleos voláteis em plantas de Aniba rosaeodora Ducke e Aniba canelilla (Kunth) Mez (Lauraceae) - Atroch, Eva Maria Alves Cavalcanti (Instituto Nacional de Pesquisas da Amazônia - INPA, 2008)
Aniba rosaeodora Ducke (rosewood) and Aniba canelilla (Kunth) Mez. (Bark-precious), stand out among the Amazonian plant resources, such as aromatic species with many uses. The economic value of A. rosaeodora resulted in unplanned exploitation of the species, leading it to extinction. Despite the economic importance of herbs, there is still little knowledge regarding the physiology and biochemical characteristics of these species. The objective of this work was to investigate the variations in physiological characteristics and concentrations of volatile oils in the leaves, stems and roots of young plants and Aniba Aniba rosaeodora canelilla when subjected to different conditions of irradiance and water availability. To evaluate the behavior of the plants against the shut-off periods interspersed with rehydration, in general, there were aspects of the water potential, gas exchange, efficiency of photosystem II pigment contents, soluble sugars and starch content volatile oils in roots, stems and leaves, and growth. The effects of water stress on water potential and relative water content were observed from 16 days without water (p  0.05) and promoted a decrease in levels of chlorophyll as well as increased levels of carbohydrates ( p  0.05). The more efficient use of water in Aniba canelilla indicated this species to be relatively more able to tolerate drier environments. The species had a higher sugar content in the roots, being the largest oil content in the leaves. The reduced availability of water did not change the oil production and partitioning in two species, but there was a drastic reduction of leaf biomass, and greater allocation to root growth. Irreversible damage on the leaves did not prevent the recovery of plants and the resumption of growth at the end of two weeks of rehydration, when they began to see new releases leaves. To evaluate the behavior of the species against two contrasting levels of irradiance, shading 70% (from 500 to 700  mol m-2 s-1) in nurseries, and full sun (1300 to 1800  mol photons m-2 s-1 ) for three weeks, were monitored on the photosynthetic characteristics variables (A, Rd), gas exchange (gs, Ci, E) and their relations (U.S., EIUA) and the photochemical efficiency of photosystem II (Fv / Fm). The production of volatile oils in the entire plant was obtained at the end of the experiment. The species exhibited some similarities in their plasticity of the photosynthetic system to changing light environments, indicating a good capacity for acclimatization. However, A. rosaeodora was more adapted to environments of high irradiance since maintained stability in gas exchange and production of volatile oils, while A. canelilla showed a reduction in oil production under high irradiance, although the pattern of partitioning remained unchanged. The results indicate that these species have characteristics that may be important for survival in a scenario of global climate change
Keywords: Aniba rosaeodora; Aniba canelill; Fisiologia vegetal